The Role of Gut Microbiota and Use of Probiotics in the Treatment of Upper Gastrointestinal Diseases - Moon Young Lee; Suck Chei Choi; Yong Sung Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Gut microbiota have been known to play an essential role in host immunity and metabolism. Dysbiosis is associated with various gastrointestinal (GI) and other diseases such as cancers, metabolic diseases, allergies, and immunological disorders. So far, the role of gut microbiota has been studied mainly in lower GI disease but has recently been reported in upper GI diseases other than Helicobacter pylori infection, including Barrett’s esophagus, esophageal carcinoma, gastric cancer, functional dyspepsia, and nonsteroidal anti-inflammatory drug-induced small intestinal mucosal injury. Probiotics have some beneficial effect on these diseases, but the effects are strain specific.